Targeted Control of Gene Expression Using CRISPR-Associated Endoribonucleases - Sagar J. Parikh; Heather M. Terron; Luke A. Burgard; Derek S. Maranan; Dylan D. Butler; Abigail Wiseman; Frank M. LaFerla; Shelley Lane; Malcolm A. Leissring (Cells)
CRISPR-associated endoribonucleases (Cas RNases) cleave single-stranded RNA in a highly sequence-specific manner by recognizing and binding to short RNA sequences known as direct repeats (DRs). Here, we investigate the potential of exploiting Cas RNases for the regulation of target genes with one or more DRs introduced into the 3′ untranslated region, an approach we refer to as DREDGE (direct repeat-enabled downregulation of gene expression). The DNase-dead version of Cas12a (dCas12a) was identified as the most efficient among five different Cas RNases tested and was subsequently evaluated in doxycycline-regulatable systems targeting either stably expressed fluorescent proteins or an endogenous gene. DREDGE performed superbly in stable cell lines, resulting in up to 90% downregulation with rapid onset, notably in a fully reversible and highly selective manner. Successful control of an endogenous gene with DREDGE was demonstrated in two formats, including one wherein both the DR and the transgene driving expression of dCas12a were introduced in one step by CRISPR-Cas. Our results establish DREDGE as an effective method for regulating gene expression in a targeted, highly selective, and fully reversible manner, with several advantages over existing technologies.